Note on the formula of brunogeierite and the first bond-valence parameters for Ge2+ - Cempirek,J.; Groat,L.A. (Journal of Geosciences, 2013)
Brunogeierite is a rare Ge-mineral with a spinel-type structure. Inconsistences in the brunogeierite formula suggesting divalent germanium in its structure have occurred since its description. A review of the published data and bond-valence calculations show that the correct ideal end-member formula of brunogeierite is (Fe2+)2Ge4+O4. The mineral is newly classified as a nesogermanate member of the ringwoodite group (Strunz classification 9.AC.15). Formal correction of the brunogeierite formula and classification was approved by the IMA Commission on New Minerals, Nomenclature and Classification (IMA-CNMNC) as proposal IMA 11-A. To perform bond-valence calculations using divalent germanium, new bond-valence parameters for Ge2+-O (R0 = 1.778 Å, B = 0.37 Å) and Ge2+-Cl (R0 = 2.156 Å, B = 0.37 Å) were evaluated.
Keywords: germanium; spinel-type structure; ringwoodite group; bond-valence model